Building a national eye-care service in post-conflict Timor-Leste - Wing, Kristof (Bull World Health Organ, 2018)
PROBLEM: Violent conflict left Timor-Leste with a dismantled health-care workforce and infrastructure after 2001. The absence of existing health and tertiary education sectors compounded the challenges of instituting a national eye-care system. APPROACH: From 2001, the East Timor Eye Program coordinated donations and initially provided eye care through visiting teams. From 2005, the programme reoriented to undertake concerted workforce and infrastructure development. In 2008 full-time surgical services started in a purpose-built facility in the capital city. In 2014 we developed a clinical training pipeline for local medical graduates to become ophthalmic surgeons, comprising a local postgraduate diploma, with donor funding supporting master’s degree studies abroad. LOCAL SETTING: In the population of 1.26 million, an estimated 35 300 Timorese are blind and an additional 123 500 have moderate to severe visual impairment, overwhelmingly due to cataract and uncorrected refractive error. RELEVANT CHANGES: By April 2018, six Timorese doctors had completed the domestic postgraduate diploma, three of whom had enrolled in master’s degree programmes. Currently, one consultant ophthalmologist, seven ophthalmic registrars, two optometrists, three refractionists and four nursing staff form a tertiary resident ophthalmic workforce, supported by an international advisor ophthalmologist and secondary eye-care workers. A recorded 12 282 ophthalmic operations and 117 590 consultations have been completed since 2001. LESSONS LEARNT: International organizations played a pivotal role in supporting the Timorese eye health system, in an initially vulnerable setting. We highlight how transition to domestic funding can be achieved through the creation of a domestic training pipeline and integration with national institutions.